Osteoarthritis of the Wrist: Pathology, Radiology, and Treatment - Grunz, Jan-Peter; Gietzen, Carsten Herbert; Christopoulos, Georgios; van Schoonhoven, Jörg; Goehtz, Florian; Schmitt, Rainer; Hesse, Nina (Seminars in Musculoskeletal Radiology, 2021)
Osteoarthritis (OA) is a degenerative disease that can manifest in any synovial joint under certain conditions. It leads to destruction of articular cartilage and adjacent bone, as well as formation of osteophytes at the edges of afflicted joint surfaces. Regarding the wrist, typical degenerative arthritis affects particular joints at a specific patient age, due to asymmetric load distribution and repetitive microtrauma. However, in the presence of instability or systemic diseases, early-onset degeneration can also impair the range of motion and grip strength in younger patients. Although advanced stages of OA display characteristic signs in radiography, the detection of early manifestations frequently requires computed tomography or magnetic resonance imaging (in some cases with additional arthrography). If a wrist becomes unstable, timely diagnosis and precise treatment are essential to prevent rapid disease progression. Therefore, close collaboration between radiologists and hand surgeons is obligatory to preserve the carpal function of patients.
Keywords: osteoarthritis; cartilage; carpal instability; wrist